TAREKAT QA - Muhammad Cholil (IAIN Ponorogo, 2015)
Abstract: The term of tarekat in Islamic study is widely known in various circles. Especially in recent years, many congregations have sprung up one after the other meets Islamic studies. One of the most famous institutes is Qa>diriyah wa Naqshabandiyah. This tarekat has spread too many regions both within the general public and at Islamic boarding school. Islamic boarding school which is the framework of Islamic education system, in which there are classic teaching models belonging salafi, by learning Islamic classical words and deepening of Sufism, as well as boarding school founded by Sheikh Imam Muhadi named